Implementation of Entrustable Professional Activities into a General Surgery Residency - Stahl, Christopher C. (J Surg Educ, 2020)
OBJECTIVE: Concerns over resident ability to practice effectively after graduation have led to the competency-based medical education movement. Entrustable Professional Activities (EPAs) may facilitate competency-based medical education in surgery, but implementation is challenging. This manuscript describes one strategy used to implement EPAs into an academic general surgery residency. DESIGN, SETTING, PARTICIPANTS: A mobile application was developed incorporating five EPAs developed by the American Board of Surgery; residents and faculty from the Departments of Surgery, Emergency Medicine, and Hospital Medicine at a single tertiary care center were trained in its use. Entrustment levels and free text feedback were collected. Self-assessment was paired with supervisor assessment, and faculty assessments were used to inform clinical competency committee entrustment decisions. Feedback was regularly solicited from app users and results distributed on a monthly basis. RESULTS: 1720 microassessments were collected over the first 16 months of implementation; 898 (47.8%) were performed by faculty with 569 (66.0%) matched pairs. Engagement was skewed with small numbers of high performers in both resident and faculty groups. Continued development of resident and faculty was required to sustain engagement with the program. Nonsurgical specialties contributed significantly to resident assessments (496, 28.8%). CONCLUSION: EPAs are being successfully integrated into the assessment framework at our institution. EPA implementation in surgery residency is a long-term process that requires investment, but may address limitations in the current assessment framework.